A Pt and Pd bimetal nanowire based stereoselective sensor for the discrimination of ascorbic acid and isoascorbic acid. Issue 15 (28th March 2018) - Ma, Jiao; Yang, Chengcheng; Zhu, Shu; Song, Jinyi; Fu, Yingzi
Abstract : A simple Pt and Pd bimetal nanowire based stereoselective sensor for the recognition of ascorbic acid and isoascorbic acid. Abstract : In this paper, a simple stereoselective sensing platform for the recognition of ascorbic acid (AA) and isoascorbic acid (IAA) was fabricated via immobilizing HS-β-cyclodextrin (HS-β-CD) on the surface of nanocomposite modified glassy carbon electrodes (GCEs). The nanocomposites were prepared using Pt and Pd bimetal nanowires (Pt–PdNWs) and reduced graphene oxide (rGO). The preparation process was characterized by scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDX), cyclic voltammetry (CV) and differential pulse voltammetry (DPV). After the modified electrodes interacted with the analytes, obvious differences in the peak currents of AA and IAA were obtained, hinting at the ability of the proposed sensor to recognize AA and IAA. This sensor with simple preparation, a rapid response, and excellent stability and reproducibility provided a promising perspective to recognize and determine AA and IAA.